Optimizing Green Waqf as a Solution to Overcome Environmental Crisis - Anwar, Khairul; Sarasi, Vita; Ubaidillah, Ubaidillah; Masnu'ah, Siti; Wahidah, Nurul (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Islam 45, 2025)
The environmental crisis has been a problem for a long time, in fact environmental degradation is getting worse from year to year. One solution to minimize environmental damage is green waqf. The aim of this research is to describe and analyze the implementation of green waqf in Indonesia, as well as analyze the reasons why green waqf can be a solution to environmental damage. This research falls into the category of library research or